Design of a wireless charging system in DC microgrids with accurate output regulation and optimal efficiency - Li, Chenchen; Wang, Kaiyuan; Mao, Yuan (Frontiers in Electronics, 2023)
This paper presents a general circuit and control design method for wireless power transfer (WPT) systems in DC microgrids to achieve optimal power transfer efficiency, while maintaining accurate output voltage regulation. An auxiliary inductance is added at the transmitter resonator to form a current sink to ensure zero voltage switching (ZVS) of the primary-side full-bridge inverter with even extreme-light load conditions. Besides, an adaptive proportional-integral (PI) controller is adopted to track the output voltage references by regulating the phase shift angle of the phase shift control for the full-bridge inverter. The coefficients of the adaptive PI controller are determined by the inductance of the auxiliary inductance. Both simulation and experimental results have validated the effectiveness of the proposed circuit and control design in achieving optimal efficiency and output voltage regulation for WPT systems in DC microgrids with source and load variations.